Twofold normalization of the cyclic creep curve of plain and steel-fiber reinforced concrete and its application to predict fatigue failure. (March 2019) - Blasón, S.; Poveda, E.; Ruiz, G.; Cifuentes, H.; Fernández Canteli, A.
Highlights: ε - N relation identified as a damage process analytically defined by a Weibull cdf. Twofold normalization, in ε and N, of cyclic creep curves. Weibull fit to ε - N curves allows probabilistic analysis and limit state proposal. Novel criterion for predicting the entire cyclic creep curves and fatigue life. Validated against 65 cyclic creep curves of plain and fiber reinforced concrete. Abstract: The cyclic creep curve or ε - N curve recorded in the fatigue test of concrete contributes to more reliable prediction of the fatigue lifetime and its scatter. Such information is compatible with that provided from the lifetime tests ( S - N field) thus reinforcing the potential information related to failure of structural concrete elements under fatigue. First, the normalization of the final number of cycles for each test provides an excellent fit thus allowing the ε - N curves to be identified as cumulative distribution functions of the Weibull family. This fact points out the probabilistic character of the deformation accumulation process or that of the micro-fractures of the "primary elements" in the specimen or component concrete bulk. A second normalization, this time referred to the stress range, would facilitate the whole extension of the procedure regardless of the loading level to which the concrete is subjected. In this way, the conventional probabilistic assessment of the S - N field is enhanced by means of the fracture criterion based on the strain-normalizing model. The application of the procedure to concrete mixes with various percentages of steel-fiber reinforcement provides direct reference criteria of easier interpretation as being based on parameters exhibiting twofold meaning, physical and probabilistic. This allows a new limit state criterion to be established on a probabilistic basis and, consequently, higher reliability in the fatigue lifetime prediction of concrete with and without fiber reinforcement to be achieved.